2012
DOI: 10.4049/jimmunol.1102397
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionary View of the Mechanism for Immune and Genome Diversity

Abstract: An ortholog of activation-induced cytidine deaminase (AID) was, evolutionarily, the first enzyme to generate acquired immune diversity by catalyzing gene conversion and probably somatic hypermutation (SHM). AID began to mediate class switch recombination (CSR) only after the evolution of frogs. Recent studies revealed that the mechanisms for generating immune and genetic diversity share several critical features. Meiotic recombination, V(D)J recombination, CSR, and SHM all require H3K4 trimethyl histone modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 71 publications
0
40
0
Order By: Relevance
“…However, it is now clear that conservation between E. coli and the higher eukaryotes is limited, and that many mammalian specific factors and reactions are necessary for the whole BER pathway. In addition, the activity of BER to ''edit'' small base adducts and damage is utilized for nonrepair activity in the cells, for example, inducing hypermutability in immunoglobulin genes (74) and maintaining demethylated status of cytosine in the genome (32,54,63,118). Conversely, it can also be argued that the high conservation of essential BER genes from prokaryotes to humans underscores the importance of BER for maintenance of genome integrity.…”
Section: Dna Base Excision Repairmentioning
confidence: 99%
“…However, it is now clear that conservation between E. coli and the higher eukaryotes is limited, and that many mammalian specific factors and reactions are necessary for the whole BER pathway. In addition, the activity of BER to ''edit'' small base adducts and damage is utilized for nonrepair activity in the cells, for example, inducing hypermutability in immunoglobulin genes (74) and maintaining demethylated status of cytosine in the genome (32,54,63,118). Conversely, it can also be argued that the high conservation of essential BER genes from prokaryotes to humans underscores the importance of BER for maintenance of genome integrity.…”
Section: Dna Base Excision Repairmentioning
confidence: 99%
“…Because AID is known to introduce DNA cleavage in a limited number of non-Ig genes such as oncogene c-myc, AID targets are restricted (20). There are only a small number of enzymes that can cause DNA damage (genotoxic activity) in a transcription-dependent manner.…”
mentioning
confidence: 99%
“…Because the AID C-terminal mutants were all shown to be monomeric, their wide distribution along the gradient suggested that some of the monomers associated with other proteins and RNAs. Collectively, these results showed that AID distributed in the LMW region could be subdivided into a narrow region of exclusive monomer (fractions 3-4) and a broader region of monomer and dimer (fractions [5][6][7][8][9][10][11][12] and that the HMW fractions of AID seemed to contain dimers.…”
Section: Detection Of Apobec Homodimer Formation By the Monomeric Kusmentioning
confidence: 77%
“…In the present study, we demonstrated that specific AID-associated RBPs have the potential to direct AID's function toward either DNA cleavage or recombination. Because CSR recombination can be regulated at either the S-S synapse or the DNA end-processing repair phase (6,11,12), we speculate that at least two independent mRNAs are involved (7,11,60). Thus, it is reasonable to propose that distinct RBPs are involved in AID-RNP complex formation and that their KD affects different stages of CSR.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation